Differences in the chromatin structure and cis-element organization of the human and mouse GATA1 loci: implications for cis-element identification. - Valverde-Garduno, V; Guyot, B; Anguita, E; Hamlett, I; Porcher, C; Vyas, P (2004)
Cis-element identification is a prerequisite to understand transcriptional regulation of gene loci. From analysis of a limited number of conserved gene loci, sequence comparison has proved a robust and efficient way to locate cis-elements. Human and mouse GATA1 genes encode a critical hematopoietic transcription factor conserved in expression and function. Proper control of GATA1 transcription is critical in regulating myeloid lineage specification and maturation. Here, we compared sequence and systematically mapped position of DNase I hypersensitive sites, acetylation status of histone H3/H4, and in vivo binding of transcription factors over approximately 120 kilobases flanking the human GATA1 gene and the corresponding region in mice. Despite lying in approximately 10 megabase (Mb) conserved syntenic segment, the chromatin structures of the 2 homologous loci are strikingly different. The 2 previously unidentified hematopoietic cis-elements, one in each species, are not conserved in position and sequence and have enhancer activity in erythroid cells. In vivo, they both bind the transcription factors GATA1, SCL, LMO2, and Ldb1. More broadly, there are both species- and regulatory element-specific patterns of transcription factor binding. These findings suggest that some cis-elements regulating human and mouse GATA1 genes differ. More generally, mouse human sequence comparison may fail to identify all cis-elements.